Whether Different Estrus Synchronization Protocols Modulate Fertility Plasma Progesterone and Metabolic Profile in Repeat Breeder Buffaloes? - Prajapati, J. P.; Patel, D. M.; Dhami, A. J.; Sarvaiya , N. P.; Prajapati, A. R. (International Journal of Livestock Research, 2019)
This study was undertaken on 50 cyclic repeat breeder buffaloes under field conditions to evaluate the efficacy of four estrus synchronization protocols, viz. Doublesynch, Estradoublesynch, Ovsynch and Ovsynch Plus (10 animals in each protocol, and in control group). The object was to study the conception rates at induced estrus with fix timed AI and to monitor the plasma progesterone, protein and cholesterol profile at different time intervals during treatment and day 12 post-AI. All the animals received pre-synchronization treatment, i.e., Inj. 100 mg ivermectin s/c, Inj. tono-vita 20 ml, single shot Inj. enrofloxacin 40 ml i/m, and multi-minerals bolus 1 daily for 7 days. The conception rates achieved at induced estrus (FTAI) were 40.0, 50.0, 60.0 and 60.0 % with Doublesynch, Estradoublesynch, Ovsynch and Ovsynch Plus protocol, respectively, and 20% in control group. The plasma progesterone concentrations monitored on day 0 (start of treatment), 7/9 (PGF2α injection), 10/12 (FTAI) and on day 12 post-AI revealed significant (p<0.01) effect of sampling days in all four protocols with higher values on day of PGF2α injection and on day 12 post-AI compared to other days. Moreover, the plasma progesterone concentrations were significantly (p<0.05) higher in conceived than the non-conceived buffaloes on day 12 post-AI in all four protocols. The mean plasma protein and cholesterol profile neither varied significantly between days in any of the protocols nor between the protocols, except that the animals under Doublesynch protocol had significantly higher pooled protein value as compared to Ovsynch and Ovsynch Plus protocols. The conceived buffaloes had significantly (p<0.05) lower mean values of plasma protein under Ovsynch protocol (5.83±0.10 vs. 6.28±0.09 g/dl) and cholesterol under Estradoublesynch protocol (63.47±1.86 vs. 73.52±2.34 mg/dl) than their counterparts. It was concluded that all four hormonal protocols modulated plasma progesterone profile and improved conception rates in cyclic buffaloes without altering plasma protein and cholesterol profile, the maximal benefit was with Ovsynch and Ovsynch Plus protocols.